Criteria for Measuring Intelligent Systems Quality in the Context of Contemporary International Standards - Mansoor N. Ali (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Intelligent systems are more common in many facets of modern life, and whether they succeed or fail largely depends on how well they are made and how strictly they follow standards. First, standards must be established and evaluated for Intelligent systems. Organizations struggle to deploy itelligent systems efficiently because they lack explicit quality requirements. A crucial component of quality assurance is selecting the appropriate standards. quality metrics for intelligent systems will be defined. This research study examines the traits, creation, and development processes of Intelligent systems. It defines the term quality Intelligent Systems. It discusses the fundamental standards and procedures for determining the caliber of quality metrics for intelligent systems and the factors that have the most significant bearing on that caliber. This study addresses intelligent system quality, measures it and how it may be regulated, and illustrates the necessity for quality ISs as they become essential to everyday interactions and activities.